2001
DOI: 10.1021/bi010469m
|View full text |Cite
|
Sign up to set email alerts
|

Site-Directed Mutation of the Highly Conserved Region near the Q-Loop of the Cytochrome bd Quinol Oxidase from Escherichia coli Specifically Perturbs Heme b595

Abstract: Cytochrome bd is one of the two quinol oxidases in the respiratory chain of Escherichia coli. The enzyme contains three heme prosthetic groups. The dioxygen binding site is heme d, which is thought to be part of the heme-heme binuclear center along with heme b(595), which is a high-spin heme whose function is not known. Protein sequence alignments [Osborne, J. P., and Gennis, R. B. (1999) Biochim. Biophys Acta 1410, 32--50] of cytochrome bd quinol oxidase sequences from different microorganisms have revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
59
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 56 publications
4
59
0
Order By: Relevance
“…This is the E445A mutant of subunit I (CydA) of cytochrome bd from Escherichia coli (35). Previous analysis concluded that heme b 595 is either partially or completely absent from the E445A mutant (35). In the current work, it is shown that the E445A oxidase preparations actually still retain the heme, but this heme remains in the ferric state, even in the presence of a strong reductant (dithionite).…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…This is the E445A mutant of subunit I (CydA) of cytochrome bd from Escherichia coli (35). Previous analysis concluded that heme b 595 is either partially or completely absent from the E445A mutant (35). In the current work, it is shown that the E445A oxidase preparations actually still retain the heme, but this heme remains in the ferric state, even in the presence of a strong reductant (dithionite).…”
mentioning
confidence: 64%
“…E. coli cells were obtained from GO105͞ pTK1 and GO105͞pTK1͞E445A strains (35). Both the WT and the E445A mutant cytochrome bd oxidases were purified as described (36), but the second (hydroxyapatite) chromatographic step was omitted as it can cause destabilization and substantial degradation of heme b 595 in the E445A mutant enzyme (35).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations